Informal housing reconstruction in the central district of Semarang city, Indonesia - Loekman Mohamadi; Lefebvre, Bernard G.; Whitney, Joseph B. R.; Fukushima, Shigeru; Overseas Training Office (OTO) Government of Indonesia (Bangkok : Asian Institute of Technology, 1994)
Looking current situation of urban informal housing in inner city, it found that a combination of market pressures and public interventions had consequently threatened the urban poor. The poor have been severely affected by commercial redevelopment. Since they mostly depend on job opportunities in inner city, makes peripheral rehousing option is unfavorable solution, even assuming that administrations had capacity to produce as much new housing would be needed. Letting urban poor to still stay in their unplanned settlement by giving tenure security and improving infrastructure through Kampung Improvement Program (KIP) was not the best possible solution. After KIP had already been implemented, they fell security in tenure situation and started to densify their settlement, due to invest more on housing. This continuous construction of the houses without supported by the sufficient infrastructures have lead this area to re-deterioration. However, in lines with the Municipality Master Plan, this urban informal housing area should be developed as part of the urban redevelopment. In trying to find a solution of the problems, this study carried out the survey to recognize the characteristic of the study area and to seek the possibility in improving this urban settlement. The land sharing is introduced as an alternative to reconstruction the urban informal housing, because it is able to accommodate the interests of the Government, a private sector, and communities. Since the Government do not have enough funds to support a reconstruction project within this area that is as part of the urban redevelopment, maximizing an internal cross-subsidy by selling part of area to a private investor can reduce the total cost of the reconstruction project, at the end, the communities can afford the cost of housing units and the Government can conduct the urban redevelopment.
A thesis submitted in partial fulfillment of the requirement for the degree of Master of science
Thesis (M.Sc.) - Asian Institute of Technology, 1994
Keywords: Housing rehabilitation -- Indonesia -- Semarang; Buildings -- Indonesia -- Semarang -- Repair and reconstruction